Gains from Improved Technology Adoption in Disadvantaged Regions: Evidences from Bundelkhand Region - SAXENA, RAKA; KANWAL, VINITA; KHAN, MOHDARSHAD; VERMA, SUMAN; B, GURURAJ (The Indian Journal of Agricultural Sciences, 2022)
The study explored the status and determinants of technology adoption in terms of shifting towards high yieldingvarieties, micro-irrigation and mechanisation in Bundelkhand zone. The study is based on a field survey conductedin the Jhansi district of Bundelkhand region in 2018–19. Bundelkhand is a water scarce area of the country andneeds policy interventions in the form of efficient water utilization and enhanced production. The results indicatethat despite least adoption of sprinkler in the region, micro-irrigation has resulted in water use conservation andimproved yields in comparison to conventional irrigation method. The findings revealed that age, income fromcultivation, possession of MGNREGA job card and membership of any local and village level organization had aconsiderable impact on the decision to adopt improved agricultural varieties and micro-irrigation implying that thesecurity nets provided in any form motivates the households to adopt improved technology. Size of operated land,income from non-agricultural activities and possession of Kisan Credit Card are the significant factors in case offarm mechanisation.